Synthesis and prospective study of the use of thiophene thiosemicarbazones as signalling scaffolding for the recognition of anions - Raposo, M. Manuela M. (2010)
A family of phenyl-thiosemicarbazone dyes have been prepared and their interactions with anions monitorized via UV-Vis, fluorescence and 1H NMR titrations. Additionally quantum chemical calculations and electrochemical studies completed the studies carried out. The phenyl-thiosemicarbazone dyes show a modulation of their hydrogen-bonding and electron-donating capabilities as a function of the chemical groups attached and display two different chromo-fluorogenic responses towards anions in acetonitrile solutions. The more basic anions fluoride and cyanide are able to induce the dual coordination-deprotonation processes for all the receptors studied, whereas acetate only interacts with receptors 2, 3, 6, 7, 8, 9 and dihydrogen phosphate displays sensing features only with the more acidic receptors 6. Coordinative hydrogen bonding interactions is indicated by a small bathochromic shift, whilst deprotonation results in the appearance of a new band at ca. 400-450 nm corresponding to a colour change from colourless-yellow to yellow-red depending on the receptor. In the emission fluorescence, hydrogen bonding interaction is visible through the enhancement of the emission band, whereas deprotonation induced the growth of a new red-shifted emission. The chromo-fluorogenic behaviour could be explained on the basis of the deprotonation tendency of the binding sites and the proton affinity of the anions. PM3 and 1H NMR calculations are in agreement with the existence of the dual complexation-deprotonation process, whereas both studies are in discrepancy in relation to which is the proton involved in the deprotonation. Electrochemical studies carried with receptor 3 showed a quite complex redox behaviour and anodic shifts of the reduction peaks in the presence of the basic anions fluoride, cyanide and acetate.